Factors Influencing Serum Homocysteine Levels in Postmenopausal Osteoporotic Females – Comparison to Urinary Collagen Crosslinks –. (3rd July 2019) - Ohishi, Tsuyoshi; Fujita, Tomotada; Nishida, Tatsuya; Asukai, Mitsuru; Suzuki, Daisuke; Sugiura, Kaori; Matsuyama, Yukihiro
ABSTRACT: Purpose : The correlation between serum levels of homocysteine and bone mineral density remains controversial. The aim of this study was to identify the potential factors associated with the levels of serum total homocysteine (S-Hcy) and urinary N-terminal telopeptide of type I collagen (U-NTX) in female osteoporotic patients. Materials and Methods : This cross-sectional study included 163 female osteoporotic patients, aged between 48 and 91 years, who had never been treated with anti-osteoporosis therapy. Background data including spine and hip bone mineral density, ongoing therapy for the metabolic disease, aortic calcification score as evaluated by lateral lumbar X-ray film, and recent fragility fracture history were obtained. S-Hcy, U-NTX levels, and creatinine clearance were measured. Results : Multiple linear regression analysis revealed a significant correlation between S-Hcy levels and aortic calcification score ( p = 0.022), creatinine clearance ( p = 0.004), and recent fracture history (within 1 year after fracture) ( p = 0.028); conversely, U-NTX levels correlated significantly with total hip bone mineral density ( p < 0.0001) and recent fracture history (p = 0.0007). Conclusions : S-Hcy levels had no correlation with bone mineral density, but were associated with the degree of aortic calcification, renal function, and fracture events. These confounding factors should be taken into consideration when the relationship between S-Hcy and bone mineral density is discussed.